2020
DOI: 10.3389/fimmu.2020.558169
|View full text |Cite
|
Sign up to set email alerts
|

Topographical Distribution and Spatial Interactions of Innate and Semi-Innate Immune Cells in Pancreatic and Other Periampullary Adenocarcinoma

Abstract: Background: The clinical management of pancreatic and other periampullary neoplasms remains challenging. In contrast to other cancer types, immunotherapies are largely ineffective, and the reason for the deprived immune response and the immune inhibiting cellular composition is only fragmentarily understood. The aim of this study was to comprehensively map the abundance, topographic distribution and spatial interaction of innate and innate-like immune cells in the tumor microenvironment of periampullary adenoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
(56 reference statements)
0
23
0
Order By: Relevance
“…Moreover, the overall survival and therapeutic efficiency is strongly linked to the presence and distribution of immune cells within the TME. Recently, two retrospective studies evaluating pancreatic tumor infiltration by innate and adaptive immune cells found an association between prolonged survival and presence of CD4+ and CD8+ T cells as well as the NKT cells and their interaction with macrophages [ 39 , 40 ]. Indeed, the immune system recognizes and eliminates tumor cells by exerting a selective pressure on tumor cells attempting to escape immune surveillance.…”
Section: Immune Regulation By Ecm Proteins In Digestive Cancersmentioning
confidence: 99%
“…Moreover, the overall survival and therapeutic efficiency is strongly linked to the presence and distribution of immune cells within the TME. Recently, two retrospective studies evaluating pancreatic tumor infiltration by innate and adaptive immune cells found an association between prolonged survival and presence of CD4+ and CD8+ T cells as well as the NKT cells and their interaction with macrophages [ 39 , 40 ]. Indeed, the immune system recognizes and eliminates tumor cells by exerting a selective pressure on tumor cells attempting to escape immune surveillance.…”
Section: Immune Regulation By Ecm Proteins In Digestive Cancersmentioning
confidence: 99%
“…Spatial immune infiltration has become a factor of interest for immunotherapy of solid tumors. Solid tumors have been described to exhibit both inter-and intratumoral spatial heterogeneity in multiple studies (60)(61)(62)(63). One classification schema sorts areas into immune inflamed, immune excluded and immune desert, with unique molecular features to each spatial subtype (64).…”
Section: Tumor Microenvironment Structurementioning
confidence: 99%
“…However, categorization of tumors based on immune infiltration to this point has focused heavily on differential T cell infiltration, with less emphasis on the spatial heterogeneity of other cell types ( 65 ). The precise spatial distribution of NK cells in patient tumors is poorly examined in the literature, though studies have confirmed that NK cells are able to localize to tumor tissue ( 61 , 66 ). A study using multiplex IF staining of tissue microarrays from periampullary adenocarcinomas revealed that CD56 + NKp46 + NK cells tend to be confined to the stromal compartment rather than infiltrating tumor nests ( 61 ).…”
Section: Introductionmentioning
confidence: 99%
“…We used two IHC panels, each consisting of antibodies to five immune markers, for visualization of adaptive and innate immune cells. After cell segmentation of digitized tissue sections, the co-expression patterns of these markers allowed for immune cell classification into distinct subgroups (see ( 9, 11, 12 ) and Supplementary Materials and Methods) (Fig 1A). The major immune cell lineages were defined by single markers (CD4, CD8, CD45RO, CD68 and CD163).…”
Section: Main Textmentioning
confidence: 99%
“…An immune scoring system that evaluates the abundance of CD3 + and CD8 + T cells in resected tumors was recently validated as an independent prognostic factor in colon cancer stage I-III, surpassing established clinical parameters such as T and N stage (4,5). The Immunoscore®, although of proven validity, quantitates only a limited subset of anti-tumoral immune cells, but a growing body of evidence supports association of additional immune cell types, including B cells and NK cells, with better outcome (6)(7)(8)(9). In addition, T-regulatory lymphocytes and M2-polarised macrophages residing in the tumor microenvironment have been connected to tumor progression (10), suggesting protumoral effects and prognostic potential of these immune suppressive cells.…”
Section: Main Textmentioning
confidence: 99%